Perlindungan Hukum Terhadap Notaris Di Negara Kesatuan Republik Indonesia - Hernika Andriani; Samuel Yuri Ericson; Edo Pradita Mandala Putra; Daffa Dwi Prasetyo (Sekolah Tinggi Ilmu Hukum Sumpah Pemuda, 2024)
A notary is a public official who creates authentic deeds to ensure legal certainty. This task is important, but it also carries legal risks that can affect the position of notaries, both personally and professionally. This article discusses legal protection for notaries in Indonesia based on Law Number 2 of 2014 concerning the Position of Notaries and other related regulations. This protection includes legal regulations, professional protection, and law enforcement. The law clearly regulates the duties and responsibilities of notaries, while the Indonesian Notary Association assists in accompanying and protecting its members. Law enforcement officials also play a role in ensuring that legal proceedings against notaries are fair. This study concludes that legal protection is designed to balance professional responsibilities and the rights of notaries, so that the profession remains sustainable and capable of maintaining legal certainty in society